Signatures of hot carriers and hot phonons in the re-entrant metallic and semiconducting states of Moir-gapped graphene - Jubin Nathawat; Ishiaka Mansaray; Kohei Sakanashi; Naoto Wada; Michael D. Randle; Shenchu Yin; Keke He; Nargess Arabchigavkani; Ripudaman Dixit; Bilal Barut; Miao Zhao; Harihara Ramamoorthy; et al. (My University, 2023)
Abstract Stacking of graphene with hexagonal boron nitride (h-BN) can dramatically modify its bands from their usual linear form, opening a series of narrow minigaps that are separated by wider minibands. While the resulting spectrum offers strong potential for use in functional (opto)electronic devices, a proper understanding of the dynamics of hot carriers in these bands is a prerequisite for such applications. In this work, we therefore apply a strategy of rapid electrical pulsing to drive carriers in graphene/h-BN heterostructures deep into the dissipative limit of strong electron-phonon coupling. By using electrical gating to move the chemical potential through the “Moiré bands”, we demonstrate a cyclical evolution between metallic and semiconducting states. This behavior is captured in a self-consistent model of non-equilibrium transport that considers the competition of electrically driven inter-band tunneling and hot-carrier scattering by strongly non-equilibrium phonons. Overall, our results demonstrate how a treatment of the dynamics of both hot carriers and hot phonons is essential to understanding the properties of functional graphene superlattices.
Keywords: Moir pattern; Graphene research and applications